Corporate reputation management: theory and applied rating approach - Derevianko, O.H.; Дерев’янко, Олена Георгіївна (Lviv-Toruń : Liha-Pres, 2019)
The problem of research of reputation management systems (RMS) of enterprises is raised in scientific works not very frequently, being mainly a field of interest for practicing PR specialists and outsourcing consultants. In addition to the above, the following trends are obvious.
Keywords: Research Subject Categories::SOCIAL SCIENCES